Pemberdayaan Kelompok Wanita Tani (KWT) Desa Ambarketawang dalam Pengolahan Limbah Rumah Tangga - Nurul Suwartiningsih; Ambar Pratiwi; Oktira Roka Aji (Jurnal Pengabdian Pada Masyarakat, 2020)
WOMEN FARMERS EMPOWERMENT OF AMBARKETAWANG VILLAGE IN HOUSEHOLD WASTE TREATMENT. People in Ambaraketawang village have begun to have awareness about the dangers of burning rubbish and littering. However, awareness of sorting and processing household waste is still not done. Garbage is only collected and finally transferred to the TPA (Tempat Pembuangan Akhir). The purpose of this activity is to provide counseling, training and assistance in processing household waste. This activity is an effort to reduce and manage household waste into something that has a use value, especially for members of the Kelompok Wanita Tani (KWT) in processing household waste. The activity was divided into several sessions including counseling on waste sorting, training on making organic liquid fertilizer, training on making organic liquid fertilizer from local microorganisms, training on composting using the Takakura method, counseling on product quality standards, and counseling on product packaging. The results obtained from this activity are increasing knowledge and skills of participants in the processing of household waste through community empowerment.